Stability and accuracy functions in multicriteria linear combinatorial optimization problems - Libura, Marek; Nikulin, Yury (Annals of operations research, 2006)
We consider a vector linear combinatorial optimization problem in which initial coefficients of objective functions are subject to perturbations. For Pareto and lexicographic principles of efficiency we introduce appropriate measures of the quality of a given feasible solution. These measures correspond to so-called stability and accuracy functions defined earlier for scalar optimization problems. Then we study properties of such functions and calculate the maximum norms of perturbations for which an efficient solution preserves the efficiency. [PUBLICATION ABSTRACT]